Do jogo das imagens às imagens do jogo - Book analysis (Revista de Artes Marciales Asiáticas, 2016)
Review of the book Do jogo das imagens às imagens do jogo, written by professors Paulo Coêlho de Araújo and Ana Rosa Fachardo Jaqueira and published in 2008 by the Centro de Estudos Biocinéticos of the Faculdade de Ciências do Desporto e Educação Física, Universidade de Coimbra. The book studies the cultural history of capoeira through images and is a valuable contribution to the historical and sociological study of this popular Brazilian martial art.